(untitled) (Bangladesh Journal of Botany, 2019)
Comparative investigations of millisecond delayed fluorescence of chlorophyll a (msec-DF Chl a) characteristics under oxidative stress induced separately by high intensity light and methyl viologen (MV) were investigated in pumpkin leaves (Cucurbita pepo L.). The inactivation of electron transport chain of PSII was observed in both experiments. The restoration of given characteristics observed at normal illumination with photoinhibited seedlings was found to enhance under action Na-ascorbate (Na-asc). The restoration of fluorescence characteristics on treated MV seedlings was recorded only at presence of Na-asc. Effect of Naasc to restore inactivated processes is considered to be due to its ability to actively neutralize reactive forms of oxygen generated under oxidative stress. It is suggested that mechanism leading to changes of induction pattern of msec-DF Chl a of PSII has common nature in both cases.